Analysis Of Performance Improvement In Msmes In Digital Transformation Through The Role Of Human Resource Management In Mentored Partners - Risca Priba Ayu; Dheo Rimbano; Herman Paleni (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to achieve several specific objectives. These objectives are to analyse the influence of Human Resource (HR) Management systems on Micro, Small, and Medium Enterprises (MSMEs) performance, evaluate the effectiveness of training on the performance of MSMEs, examine local government policy support for active HR management, and investigate the local and global factors that influence the digitally informed technological behaviour of the nurtured partners of the Cooperatives, Small and Medium Enterprises (SMEs) Office of Lubuklinggau City. As for the latter, this refers to the Lubuklinggau City partners nurtured by the Cooperatives. This research is study-based and of the qualitative approach. The findings indicate that the digital transformation of MSMEs in Lubuklinggau City is both a significant challenge and an immense opportunity. HR management strategies are an important key to optimizing the potential of MSME actors so that they can adapt and grow in the digital era. The limitations are a relatively small scope of research and a relatively short research time limit. This research contributes to providing knowledge from an academic perspective about the role of HR management strategies, efforts to improve MSME performance, and analysis of local government policies in supporting human resource management in the Fostered Partners of the Lubuklinggau City Cooperatives, Small and Medium Enterprises Office, and the performance Improvement in MSMEs in Digital Transformation through the Role of Human Resource Management in specific subject.